(3McGjG eLfhf (B: (3eLehYI bUUjI ef COH GdacGgI hGdgRd (B/s - (3Chcajd, YHO GdMcje, s 1986- ((3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ edgehf ddfTQ hGdJhRjY,s, 2021)
(3jJMOK GdcJGH Yf TNU jOYi (B((3GHf bWjf(B) (3hdbO dbH faSg HGHf bWjf, Pdc dCf UGMHg GdhMjO GdPj Hbj dg aj OfjGg gh bW eJTQO CMHg, YhVg HHYV GdCfS Yf abOGf CH TjN hCe YLhR, bW cGf jMJc Hg bHd NQhLg ddPgGH Edi OcGfg GdbOje, OcGf dHjY GdedGHS GdeSJYedI dG jSef hdG jZfj ef LhY, cGf GdbW PGc hcd jhe, aj cd UHGM, jfJXQg hjJHYg MJi JHfGg aLYdg Qajbg GdPj jfSjg GdMGLI hGdabQ, SeGg (B((3HjQGW(B) (3HGdYQHjI (B((3bQUGf(B) (3Pdc dCfg aGbO dYjfg Gdjefi, Edi Cf cGf Gdjhe GdPj eGJ ajg GdbW GdeScjf eNJfbG HYO Cf fGe Ydjg UGMHfG NWC (B! (3aJMSQ LYaQ dehJg MSQI LYdJ Lfhfg GddGMb jSHb GdSGHb, adbH faSg HGHf bWjf JjefG HeG SeY ef CdbGH cGHf SjQjf hGHf YKjejf hcPdc JNdjOG dPcQi bWg GdeZOhQ, QZe EOQGcg Cfg LYd faSg GHfG dbW, dcfg bGd aj faSg ebfYG dgG aj bQGQ eLfhf OGe CKQg Ydjg cGdeQV GdeRef (B: ((3Cf Cchf GHfG dbW eLGRG CaVd ef Cf Cchf GHfG dEfSGf aYdG (B! (3aeG JQc dj CHj Shi GdOjhf JRjOfj gdGcG Ydi gdGc (B...)s
Keywords: (3GdCOH GdYQHj s -- (3JUeje(B.s -- (3bQf (B21s -- (3GdEeGQGJ GdYQHjI GdeJMOIs; (3GdCgGLj hGdacGgGJ GdYQHjIs -- (3bQf (B21s -- (3GdEeGQGJ GdYQHjI GdeJMOIs